2017
DOI: 10.3390/molecules22122199
|View full text |Cite
|
Sign up to set email alerts
|

Conserved Binding Regions Provide the Clue for Peptide-Based Vaccine Development: A Chemical Perspective

Abstract: Synthetic peptides have become invaluable biomedical research and medicinal chemistry tools for studying functional roles, i.e., binding or proteolytic activity, naturally-occurring regions’ immunogenicity in proteins and developing therapeutic agents and vaccines. Synthetic peptides can mimic protein sites; their structure and function can be easily modulated by specific amino acid replacement. They have major advantages, i.e., they are cheap, easily-produced and chemically stable, lack infectious and seconda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 260 publications
(294 reference statements)
1
3
0
Order By: Relevance
“…The blood-stage antimalarial vaccine candidates’ immunogenicity results described here (mainly based on P. falciparum protein conserved regions) have indicated that although moderate Ab titers are induced after a first immunization, they do not induce long-lasting protective immunity. This is consistent with our research demonstrating that, although conserved regions are functionally important for target cell binding, they are poorly recognized by host immune system due to being located far from the highly polymorphic regions used by the parasite as an evasion mechanism to distract the immune system (Patarroyo et al, 2017b); such polymorphic regions are immunodominant but confer just strain-specific immunity (Hisaeda et al, 2005; Curtidor et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The blood-stage antimalarial vaccine candidates’ immunogenicity results described here (mainly based on P. falciparum protein conserved regions) have indicated that although moderate Ab titers are induced after a first immunization, they do not induce long-lasting protective immunity. This is consistent with our research demonstrating that, although conserved regions are functionally important for target cell binding, they are poorly recognized by host immune system due to being located far from the highly polymorphic regions used by the parasite as an evasion mechanism to distract the immune system (Patarroyo et al, 2017b); such polymorphic regions are immunodominant but confer just strain-specific immunity (Hisaeda et al, 2005; Curtidor et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…This methodology has enabled testing and selecting mHABP derived from parasite life cycle stages, which has led to promising results in obtaining a highly immunogenic and protection-inducing antimalarial vaccine (Garcia et al, 2007; Rodriguez et al, 2008; Bermúdez et al, 2012; Curtidor et al, 2017). Chemically synthesized vaccines’ main advantages include their high yield, reproducibility, purity (free of contaminants, such as endotoxins), lack of secondary adverse reactions, being able to synthesize unlimited amounts and stability at room temperature for long periods of time (not requiring cold chain) (Bermúdez et al, 2008; Skwarczynski and Toth, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Peptide Synthesis and Purification. Twenty-three polymer peptides (Table 1) were modified following previously reported principles [32,33,40,41] to render them immunogenic and then synthesised using solid-phase multiple peptide synthesis following the tert-butyloxycarbonyl (t-Boc) synthesis strategy described by Merrifield [42] and modified by Houghten [43]. All peptides were derived from fully conserved and functionally relevant regions of the corresponding proteins.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, understanding MHC class II binding enables designing pharmaceutical vaccines against infectious diseases. Studying MHC-DR binding prediction has special relevance developing a peptide-based malaria vaccine which is our group’s main goal. …”
Section: Introductionmentioning
confidence: 99%